EFEKTIVITAS WILAYAH RAMAH ANAK DI KELURAHAN KUNINGAN, SEMARANG UTARA, KAITANNYA DENGAN TINGKAT KRIMINALITAS YANG DILAKUKAN ANAK - Muhammad Iftar Aryaputra; Dewi Tuti Muryati; Agus Saiful Abib (Universitas Semarang, 2017)
Child protection efforts become very important. One of the efforts made in this regard is to establish “wilayah ramah anak”. In Kota Semarang, “wilayah ramah anak” is implemented in Kelurahan Kuningan. It is hoped that this effort will not only be a way to provide protection to children but also to prevent children from doing things that are against the norm. Issues raised in this study are, (1) how the model of “wilayah ramah anak” contained in Kelurahan Kuningan?; (2) what is the correlation between the establishment of “wilayah ramah anak” with the crime committed by children ?. This research is a sociological law research. Thus, the data used are primary data supported by secondary data which then analyzed qualitatively. Based on the results of research obtained results, first, child-friendly areas in Kelurahan Kuningan basically more physical changes, especially in terms of play facilities and learning children. In addition, there are several other non-physical facilities to support existing physical facilities. Second, “wilayah ramah anak” in Kelurahan Kuningan basically not formed to reduce the crime of children in the walayah. However, indirectly, child-friendly territory can be the breaker of a child's delinquency chain by forming a new generation that avoids crime-related matters.